Implicit and Explicit Self-Identification as a Drug User in People Who Used Heroin and Methamphetamine - Chen, Jianyong; Zhang, Meng; Zhou, Jifan; Li, Xinyu; Zhang, Feng; Shen, Mowei (Frontiers in Psychology, 2021)
Implicit and explicit self-identification as a drug user specific to the substance used (e.g., viewing oneself as a drinker) have been examined, as they relate to that drug use. However, studies have rarely explored whether identifying as a “drug user” differs implicitly and explicitly for people who use different drugs and how this identification relates to drug-use behaviors or abstinence. This study examined implicit and explicit self-identification as a “drug user” and their associations with drug-use behaviors and abstinence in people who used heroin (PWUH) and people who used methamphetamine (PWUM). Forty PWUH and 35 PWUM in a rehabilitation facility completed the Single Category Implicit Association Test (SC-IAT), which evaluated implicit associations of “drug user” with “self,” and a measure of explicit self-identification as a “drug user.” Participants’ prior drug-use behaviors and current abstinence duration were assessed. PWUH demonstrated stronger implicit “self + drug user” associations and higher levels of explicit self-identification as a “drug user” than PWUM. A higher frequency of drug use was associated with higher levels of explicit drug-user self-identity, and longer abstinence duration was positively related to stronger implicit “self + drug user” associations in PWUH. The drug type of heroin (vs. methamphetamine) participants used was associated with a higher frequency of use, which in turn predicted higher levels of explicit drug-user self-identity. Given that PWUH differ from PWUM in terms of implicit and explicit self-identification as a “drug user,” it would be more appropriate to address individuals’ drug-user self-identity according to the substance they use rather than as a collective group.